Wawasan Al-Qur’an Terkait Kemiskinan (Studi Tafsir Tematik) - Ranya Fariha Nasaruddin; Rahmi Damis; Hasyim Haddade (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Poverty is a constant humanitarian problem spanning the history of human civilization. Despite the rapid development of modernization instruments and material progress, the distributive inequality of wealth continues to generate striking disparities. This study aims to formulate a comprehensive Quranic conception of poverty using the Tafsir Maudhu'i (thematic) approach. The focus of the study is directed at three main pillars: the semantic nature of poverty terms (specifically the term miskin), the causal factors of poverty, and the integrative solutions offered by the Quran. The results of the analysis show that the word miskin is rooted in the meaning of stillness or lack of movement (sakana), indicating an economic helplessness that leaves an individual